Long Term Amendment with Fresh and Composted Solid Olive Mill Waste on Olive Grove Affects Carbon Sequestration by Prunings, Fruits, and Soil - Regni, Luca; Nasini, Luigi; Ilarioni, Luana; Brunori, Antonio; Massaccesi, Luisa; Agnelli, Alberto; Proietti, Primo (Frontiers in Plant Science, 2017)
The soil amendment with organic wastes represents a way to increase the soil fertility and the organic carbon (C) stored in the agro-ecosystems. Among the organic waste materials produced by agricultural and industrial activities, olive mill wastes derived from the olive oil extraction process may represent a suitable soil amendment. The aim of the study was to evaluate the effect of fresh (SOMW) or composted mixture of SOMW and shredded olive tree prunings (C-SOMW+P) on the vegetative and productive activities of olive trees, on the C stored in the tree non-permanent structures (prunings and fruits) and in the soil. The plots treated with SOMW or C-SOMW+P showed higher vegetative and productive activities than the untreated plots, and this was attributed to the higher total N and availability of P and K supplied by the amendments. Consequently, treatments increased the C sequestered in the tree non-permanent structures than in the control trees. However, no significant different effect between SOMW and C-SOMW+P treatments was found for the C stored in prunings and fruits, whereas it was evident a stronger influence of C-SOMW+P than SOMW on soil C sequestration. Indeed, about 50% the C supplied by the treatment with C-SOMW+P was sequestered in the olive grove system, with more than 90% of the sequestered C stored into the soil. The low amount of C sequestered in the soil following the addition of SOMW was attributed to its richness of moisture and easily degradable compounds that triggered the mineralization processes controlled by the soil microbial community. Although the 8 years of amendment produced a higher fruit yields than the control, no difference occurred between the characteristics and the oil content of the olive fruits. Only the total phenol content for the oil obtained from the SOMW-treated plots was significantly higher. The other considered fruit characteristics did not show significant differences.